What Determines the ZEW Indicator? - Felix P. Hüfner; David Lahl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
This paper analyzes which factors are driving the ZEW Indicator of Economic Sentiment. Using the results of a poll among survey participants as well as Granger causality tests we identify three groups of influence factors: other sentiment indicators, financial variables and real economy data. In a second step these factors are used to estimate out-of-sample forecasts for the ZEW Indicator. We find that a simple model that includes German manufacturing order data, the German yield structure and the US Consumer Confidence indicator as explanatory variables is able to outperform a naive univariate benchmark model as well as the consensus forecast for the ZEW Indicator as published by news agencies.
Keywords: E32; E37; 330; leading indicators; Germany; zew; forecasting; Konjunkturindikator; Geschäftsklima; Konjunkturprognose; Prognoseverfahren; Deutschland